Strategi Digital Marketing dalam Meningkatkan Kinerja Pemasaran Produk Alat Kesehatan: Studi Kualitatif di Era Transformasi Digital - Meta Mediana; Wawan Sudira; Romauli; Yen Efawati (PT Wahana Global Education, 2026)
Digital transformation has significantly reshaped marketing practices in the medical device industry, requiring adaptive and technology-driven strategies. This study aims to analyze digital marketing strategies and identify the factors influencing their effectiveness in improving marketing performance of medical device products. This research employs a qualitative approach grounded in the interpretivist paradigm using an intrinsic case study method. Data were collected through in-depth interviews, participant observation, and documentation, applying triangulation techniques to ensure data validity. The findings reveal that effective digital marketing strategies include the utilization of social media, educational content marketing, search engine optimization (SEO), and the use of marketplace and e-commerce platforms to expand market reach. Furthermore, the use of data analytics plays a crucial role in supporting precise and efficient marketing decision-making. The implementation of these strategies contributes to increased sales, brand awareness, customer engagement, and broader market coverage. The success of these strategies is influenced by both internal and external factors while facing challenges such as regulatory constraints and digital literacy limitations. This study concludes that a trust-based marketing approach emphasizing education and transparency is the key to enhancing marketing performance in the medical device industry in the digital era. Keywords: Brand Awareness, Content Marketing, Digital Marketing, Marketing Performance, Trust-Based Marketing